Effects of Adolescent Ethanol Exposure on Sleep in Adults Rats - Criado, José R. (2008)
Although adolescent ethanol (EtOH) exposure has been associated with long-lasting changes in brain function, little is known as to whether EtOH exposure during adolescence alters sleep and cortical arousal. This study examined protracted alterations in sleep in adult rats exposed to EtOH during adolescence. Adolescent male Wistar rats were exposed to EtOH vapor for 12 hr/day for five weeks. Cortical electroencephalograms (EEGs) were obtained during 4-hr recording sessions after five weeks of withdrawal from EtOH. Adolescent EtOH exposure significantly reduced the mean duration of slow-wave sleep (SWS) episodes and the total amount of time spent in SWS in EtOH-exposed rats, compared to controls. Spectral analysis revealed that adolescent EtOH exposure significantly increased cortical peak frequencies during SWS in the 2-4 Hz, 4-6 Hz and 6-8 Hz bands. Taken together, our findings suggest that chronic EtOH exposure in adolescent rats reduces measures of SWS, an effect also seen as part of normal aging. Although the cellular and molecular mechanisms mediating the consequences of EtOH exposure on the aging process are not known, the similarities between adolescent EtOH exposure and aging merits further investigation.